2021
DOI: 10.1186/s12913-021-06981-5
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of burnout and professional turnover intentions among Canadian physicians: application of the job demands-resources model

Abstract: Background Burnout among physicians is growing at an exponential rate and many are leaving the profession. Nevertheless, the specific antecedents and intermediary stages involved in predicting their professional turnover intentions are not fully clear. Purpose We apply the Job Demands-Resources model and investigate an innovative model which predicts physician burnout and its ultimate consequences on professional turnover intentions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 45 publications
3
24
0
1
Order By: Relevance
“…This suggests clinician’s wellbeing is significantly associated with perceptions of demand, how well resourced their mental health service is felt to be, and whether they feel they are provided with support. All these factors are recognised to constitute significant sources of stress and are understood as contributing factors in burnout research more widely [ 45 47 ]. The findings of this research are consistent with other studies where staff shortages, inadequate resourcing and a disjunction between the views and priorities of managers are emphasised as contributing to burnout [ 45 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests clinician’s wellbeing is significantly associated with perceptions of demand, how well resourced their mental health service is felt to be, and whether they feel they are provided with support. All these factors are recognised to constitute significant sources of stress and are understood as contributing factors in burnout research more widely [ 45 47 ]. The findings of this research are consistent with other studies where staff shortages, inadequate resourcing and a disjunction between the views and priorities of managers are emphasised as contributing to burnout [ 45 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential consequences of low job satisfaction was manifest in the respondents’ views concerning desire and plans to leave their work. There is an acknowledged relationship between low job satisfaction and intentions to leave medicine [ 51 , 52 ] as well as between intentions to leave medicine and rates of stress and burnout in doctors [ 47 ]. While understanding the relationship between burnout and work stress and intentions to leave psychiatry was not a specific focus of the research, the association found between low job satisfaction and thoughts of and intentions to leave work is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also contribute to a better understanding of how stress, particularly cognitive type stress, affects turnover intentions. Most studies on stress and its effects on turnover intentions focus on a chronic type of stress, particularly burnout (Hayes et al, 2012;Chênevert et al, 2021); and fewer have addressed the relationship with cognitive symptoms of stress (e.g., working memory difficulties, indifference to work, information overload and impaired concentration) (Rantanen et al, 2021). Cognitive stress has significant effects on the quality of attention and the performance of workers at healthcare organizations, as it increases the likelihood of errors at work and impairs the sense of self-efficacy, which has also been linked to increased intentions to quit (Buchbinder et al, 2001).…”
Section: Not Confirmedmentioning
confidence: 99%
“…Burnout in medical doctors can represent a high cost, as it is also related to early departures [ 4 , 12 ] and an increased desire to change professions [ 16 ]. Medical turnover about job dissatisfaction increases the costs of recruiting and retaining doctors [ 12 , 17 ] and decreases cohesion in the institution [ 18 ].…”
Section: Introductionmentioning
confidence: 99%